Chemoenzymatic One-Pot Process for the Synthesis of Tetrahydroisoquinolines - Andreas Sebastian Klein (MDPI AG, 2021)
1,2,3,4-Tetrahydroisoquinolines form a valuable scaffold for a variety of bioactive secondary metabolites and commercial pharmaceuticals. Due to the harsh or complex conditions of the conventional chemical synthesis of this molecular motif, alternative mild reaction pathways are in demand. Here we present an easy-to-operate chemoenzymatic one-pot process for the synthesis of tetrahydroisoquinolines starting from benzylic alcohols and an amino alcohol. We initially demonstrate the oxidation of 12 benzylic alcohols by a laccase/TEMPO system to the corresponding aldehydes, which are subsequently integrated in a phosphate salt mediated Pictet–Spengler reaction with m-tyramine. The reaction conditions of both individual reactions were analyzed separately, adapted to each other, and a straightforward one-pot process was developed. This enables the production of 12 1,2,3,4-tetrahydroisoquinolines with yields of up to 87% with constant reaction conditions in phosphate buffer and common laboratory glass bottles without the supplementation of any additives.